2012
DOI: 10.1073/pnas.1205654109
|View full text |Cite
|
Sign up to set email alerts
|

The polymorphism rs944289 predisposes to papillary thyroid carcinoma through a large intergenic noncoding RNA gene of tumor suppressor type

Abstract: A genome-wide association study of papillary thyroid carcinoma (PTC) pinpointed two independent SNPs (rs944289 and rs965513) located in regions containing no annotated genes (14q13.3 and 9q22.33, respectively). Here, we describe a unique, long, intergenic, noncoding RNA gene (lincRNA) named Papillary Thyroid Carcinoma Susceptibility Candidate 3 (PTCSC3) located 3.2 kb downstream of rs944289 at 14q.13.3 and the expression of which is strictly thyroid specific. By quantitative PCR, PTCSC3 expression was strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
197
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(202 citation statements)
references
References 39 publications
2
197
2
1
Order By: Relevance
“…Recent studies have indicated that lncRNAs are transcribed from cancer risk loci and that these transcripts can play important roles in tumorigenesis. [30][31][32] Here, we used RNA-seq to identify two estrogenregulated lncRNAs (CUPID1 and CUPID2) that might contribute to the risk of developing breast cancer by modulating pathway choice of DSB repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have indicated that lncRNAs are transcribed from cancer risk loci and that these transcripts can play important roles in tumorigenesis. [30][31][32] Here, we used RNA-seq to identify two estrogenregulated lncRNAs (CUPID1 and CUPID2) that might contribute to the risk of developing breast cancer by modulating pathway choice of DSB repair.…”
Section: Discussionmentioning
confidence: 99%
“…Ingenuity Pathway Analysis (IPA) on the differentially expressed genes was conducted as described previously. 14 Expression of CUPID1 and CUPID2 in TCGA Cohort RNA-seq data from The Cancer Genome Atlas (TCGA) breast invasive carcinoma cohort (1,226 samples) were obtained from the UCSC Cancer Genomics Hub (September 30,2015). The procedures followed were in accordance with the ethical standards of the responsible committee on human experimentation (institutional and national), and proper informed consent was obtained.…”
Section: Rna-seqmentioning
confidence: 99%
“…XRCC1 plays an important role in the DNA repair pathway because it could specifically interact with nicked and gapped DNA, rapidly and transiently responds to DNA damage in cells, thus may serve as a strand-break sensor (Mani et al, 2004). In addition, XRCC1 could interact with many proteins known to be involved in BER andSSBR, so it has been proposed that XRCC1 may function as a scaffold protein able to coordinate and facilitate the steps of various DNA repair pathways (Mani et al, 2007). It is widely accepted that alterations in XRCC1 may play important roles in the process associated with the etiology of cancers because of the alteration of base excision repair functions (Monaco et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…71 The G allele of rs6983267, in addition to being related to a significantly increased risk of CRC, 72 results in more CCAT2 transcripts than the T allele, which further affects the regulation of MYC by CCAT2; thus different rs6983267 alleles can affect CCAT2 expression and function. 58 Studies examining other cancer types have shown that SNPs in the key regulatory regions of an lncRNA can alter its structural motifs 73 and may consequently affect its expression and function in malignancies, 74 additionally contributing to cancer risk. 75,76 SNPs in the cancer-associated lncRNAs could potentially have pivotal roles in colorectal tumorigenesis and progression.…”
Section: Regulation Of Lncrna Expressionmentioning
confidence: 99%